Overhead cost, price randomization, and price stickiness - Helmut Zink (Universität Konstanz, Fakultät für Wirtschaftswissenschaften und Statistik, 1994)
This paper investigates price setting when firms produce with increasing returns and customers are imperfectly informed about prices but customers can search. It is shown that there exists a unique randomization equilibrium where each customer is offered a random price by each firm known to him. If the number of firms is fixed then the expected price to be paid by a customer responds countercyclically to variations of demand per customer and it remains invariant with respect to variations of the number of customers. This price behavior corresponds well with new evidence on price behavior.
Keywords: 330; increasing returns; price stickiness; search